Association of pain after trauma with long-term functional and mental health outcomes. Issue 4 (October 2018) - Herrera-Escobar, Juan Pablo; Apoj, Michel; Weed, Christina; Harlow, Alyssa Fitzpatrick; Al Rafai, Syeda Sanam; Lilley, Elizabeth; Kasotakis, George; Brasel, Karen; Kaafarani, Haytham M.A.; Velmahos, George; Salim, Ali; Haider, Adil Hussain
Abstract : BACKGROUND: Chronic pain after trauma is associated with serious clinical, social, and economic burden. Due to limitations in trauma registry data and previous studies, the current prevalence of chronic pain after trauma is unknown, and little is known about the association of pain with other long-term outcomes. We sought to describe the long-term burden of self-reported pain after injury and to determine its association with positive screen for posttraumatic stress disorder (PTSD), functional status, and return to work. METHODS: Trauma survivors with moderate or severe injuries and one completed follow-up interview at either 6 months or 12 months after injury were identified from the Functional Outcomes and Recovery after Trauma Emergencies project. Multivariable logistic regression models clustered by facility and adjusting for confounders were used to obtain the odds of positive PTSD screening, not returning to work, and functional limitation at 6 months and 12 months after injury, in trauma patients who reported to have pain on a daily basis compared to those who did not. RESULTS: We completed interviews on 650 patients (43% of eligible patients). Half of patients (50%) reported experiencing pain daily, and 23% reported taking pain medications daily between 6 months and 12 months after injury. Compared to patients without pain, patients with pain were more likely to screen positive for PTSD (odds ratio [OR], 5.12; 95% confidence interval [CI], 2.97–8.85), have functional limitations for at least one daily activity (OR, 2.42; 95% CI, 1.38–4.26]), and not return to work (OR, 1.86; 95% CI, 1.02–3.39). CONCLUSIONS: There is a significant amount of self-reported chronic pain after trauma, which is in turn associated with positive screen for PTSD, functional limitations, and delayed return to work. New metrics for measuring successful care of the trauma patient are needed that span beyond mortality, and it is important we shift our focus beyond the trauma center and toward improving the long-term morbidity of trauma survivors. LEVEL OF EVIDENCE: Therapeutic/Care management, level III. Abstract : Supplemental digital content is available in the text.